Barriers to sexual and reproductive health communication in Southwest Ethiopia: perspectives of parents, youths, and teachers - Gizaw, Abraham Tamirat; Muktar, Sualiha Abdulkader; Wondimagegene, Yohannes Addisu; Abayneh, Mengistu; Sefere, Belay Zeleke; Tareke, Kasahun Girma; Yilma, Abebayehu N. (Frontiers in Reproductive Health, 2025)
BackgroundYouths throughout the world face considerable challenges related to their sexual and reproductive health (SRH). In Ethiopia, the adolescent and youth groups account for nearly half the population. Parents play a vital role in SRH communication. Parents’ communication with their children regarding SRH is considered an important part of adolescent development, as this contributes to optimizing safe SRH. Therefore, this study aimed to explore barriers to SRH communication from the perspectives of parents, youths, and teachers in Southwest Ethiopia.MethodsA qualitative research approach was used in four schools (two private and two public) in Jimma town. Data collection entailed 16 focused group discussions with parents and youths (15–24 years) and 12 key informant interviews with school directors, unit leaders, and school media coordinators. The interviews were audio-recorded, transcribed, and translated into English. Thematic analysis was conducted using ATLAS_ti software.ResultsParticipants recognized the crucial role parents play in SRH issues; however, only a few parents were involved in SRH communications, and there were many barriers raised by the participants. Barriers to SRH communications were parental lack of knowledge, cultural and religious beliefs, the effect of social media use, shame and stigma, and parental attitudes towards SRH communication.ConclusionsIn summary, addressing barriers to sexual and reproductive health communication between parents and youth is crucial for fostering better health outcomes. Parents should be encouraged to have open discussions with their children from an early age. High schools should implement regular SRH education sessions with healthcare providers, while youth-friendly service clubs should focus on changing attitudes towards SRH communications through social and behavioral changes in communication.